Software ecosystems – A systematic literature review - Manikas, Konstantinos; Hansen, Klaus Marius (The Journal of systems and software, 2013)
► We conducted a systematic literature review on the field of software ecosystems. ► We concluded that there little consensus on what constitutes a software ecosystem. ► Categorized the literature according to the reported result and concluded that there is few analytical models on the field of software ecosystems. ► Recognized that there is little research done in the context of real-world software ecosystems. A software ecosystem is the interaction of a set of actors on top of a common technological platform that results in a number of software solutions or services. Arguably, software ecosystems are gaining importance with the advent of, e.g., the Google Android, Apache, and Salesforce.com ecosystems. However, there exists no systematic overview of the research done on software ecosystems from a software engineering perspective. We performed a systematic literature review of software ecosystem research, analyzing 90 papers on the subject taken from a gross collection of 420. Our main conclusions are that while research on software ecosystems is increasing (a) there is little consensus on what constitutes a software ecosystem, (b) few analytical models of software ecosystems exist, and (c) little research is done in the context of real-world ecosystems. This work provides an overview of the field, while identifying areas for future research.